Acquired systemic-to-pulmonary shunts in a 6-month-old child: case report and review of the literature. (10th February 2020) - Werner, Oscar; Ovaert, Caroline; Amedro, Pascal
Abstract: The incidence of paediatric venous thromboembolism has steadily increased in the past decade, by nearly 10% per year. Deep venous thrombosis may remain completely asymptomatic during the acute phase and symptoms may occur later, due to complications. We related the case of a 9-month-old child with increasing cyanosis. A computed tomography (CT) angiography showed a thrombosis of the superior vena cava (SVC) with the development of collateral flow from the systemic to the pulmonary veins. Transcatheter shunt occlusion after SVC recanalization was successfully performed. We discussed the characteristics of these cases and the consequence on our practice in term of treatment (anticoagulation, transcatheter, intervention) and screening.